Respuesta :

Answer:

Step-by-step explanation:

This thing looks like you have to use the quadratic equation to solve it. You don't. It will factor. but you might have to guess a bit.

(3x       )(2x      )

(3x - 5 ) (2x + 7)                       How lucky is that!!?

Remove the Brackets

3x * 2x + 3x*7 - 5*2x - 35       Combine

2x*3x^2 + 21x - 10x - 35            

6x^2 + 11x - 35

So the guess turns out to be correct. Now we need to solve for the roots.

3x - 5  = 0                             Add 5 to both sides.

3x = 5                                   Divide by 3

x = 5/3

x = 1.6667

2x + 7 = 0                            Subtract 7 from both sides

2x = - 7                                Divide by 2

2x/2 = - 7/2

x = - 3.5

Answer

  • x = 1.667 or
  • x = - 3.5